Sentiment Analysis with Machine Learning Techniques and Improved J48 Decision Tree Technique - koli, Sakshi (International Journal of Computer Sciences and Engineering, 2021)
Last few years the area of social media , e- commerce, social field has seen a large increase in the web world. The product view became the basic need of today‘s world . The product reviews channel the customers and help them in making decisions regarding various available products which otherwise would bemuse them. This circumstances opened a new area of research called Opinion Mining and Sentiment Analysis. sentiment analysis is the process of determining the emotion ,feeling, and views of the people towards the piece of text, that comes under the area of blog view, article review , product review, social media buzzing etc. This research paper presents machine learning methods for detecting the sentiment expressed by movie reviews. The semantic point of reference of a review can be positive or negative.